Comparative analysis of accesses to determining the controlling Essence - I. V. Lipatova; N. V. Savina; T. V. Pluzhnikova (Учёт. Анализ. Аудит, 2022)
The permanent change in the conditions for the functioning of the public sector, the emergence of new aims and the expansion of the range of tasks to be solved, the increased interest in the issues of the effectiveness of state and municipal government in the face of uncertainty lead to the emergence of new approaches, which are largely based on the use of advanced methods and management systems that have shown their effectiveness. One of them is controlling, which originally arose in the public sector, and also had developed in the commercial sector as a part of organization’s management. The purpose of the research is to reveal its essence from the point of view of various aspects and approaches, followed by highlighting current trends in the definition of this concept, as well as its methodology based on comparison, analysis, synthesis, analogies, grouping, systemic and logical approaches. The paper summarizes domestic scientific literature in this area and presents the studying results of the controlling concepts that have developed in international practice. Based on the identified distinctive features, the authors made a conclusion about the approach to its interpretation that has developed in Russian scientific thought, the uniqueness of the concept under consideration, as well as the trends in considering its essence.